Production of Alternative LT Materials - Castillo, Maria; Piantzi, Leticia (CIEX JOURNAL, 2016)
The area of language teaching materials has been evolving continuously, starting from the design and production of very traditional materials to alternative teaching aids designed with the help of technology. In these sessions, participants will analyze the fundamentals to design alternative language teaching materials. Next, they will produce some alternative didactic materials such as: picture flash cards, posters, cartoons, books and computer based materials, among others.